Tunable multi-electron redox polyoxometalates for decoupled water splitting driven by sunlight - Cui, Li-Ping; Zhang, Shu; Zhao, Yue; Ge, Xin-Yue; Yang, Le; Li, Ke; Feng, Liu-Bin; Li, Ren-Gui; Chen, Jia-Jia (Nature communications, 2025)
It remains a great challenge to explore redox mediators with multi-electron, suitable redox potential, and stable pH buffer ability to simulate the natural solar-to-fuel process. In this work, we present a defect engineering strategy to design soluble multi-electron redox polyoxometalates mediators to construct a photocatalysis-electrolysis relay system to decouple H 2 and O 2 evolution in solar-driven water splitting. The appropriate use of vanadium atoms to replace tungsten in the Dawson-type phosphotungstate successfully regulated the redox properties of the molecular clusters. Specifically, the single vanadium substitution structure (P 2 W 17 V) possesses 1-electron redox active and sequential proton-electron transfer behavior, while the tri-vanadium substituted cluster (P 2 W 15 V 3 ) exhibits 3-electron redox active and cooperative proton electron transfer behavior. Based on the developed multi-electronic redox mediator with pH buffering capacity, suitable redox potential (0.6 V), and fast electron exchange rate, we build a photocatalysis-electrolysis relay water splitting system. This system allows for high capacity of solar energy storage through photocatalytic O 2 evolution using BiVO 4 photocatalyst and stable H 2 production with a high Faraday efficiency of over 98.5% in the electrolysis subsystem. Designing efficient redox mediators for solar-to-fuel conversion is a challenge, requiring multi-electron transfer, suitable redox potential, and stable pH buffering. Here, the authors report polyoxometalate-based mediators with defect engineering, enabling reliable solar-to-fuel conversion.